2022
DOI: 10.3389/fpsyg.2022.770927
|View full text |Cite
|
Sign up to set email alerts
|

Family Resilience and Psychological Responses to COVID-19: A Study of Concordance and Dyadic Effects in Singapore Households

Abstract: The impacts of COVID-19 may be magnified in a shared environment like the household, especially with people spending extended time at home during the pandemic. Family resilience is the ability of a family to adapt to crisis and can be a protective factor against stress and negative affect. While there have been calls to address family resilience during the pandemic, there is a lack of empirical study on its benefit. In this dyadic observational study, we sought to investigate the concordance of family members’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…A meta-analysis confirmed that resilience is a psychological resource that can support the acceleration of recovery and the mitigation of the negative effects of a crisis [ 16 ]. Moreover, recent studies conducted during the COVID-19 pandemic have identified the protective role of resilience in distress conditions among several populations, including university students [ 7 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis confirmed that resilience is a psychological resource that can support the acceleration of recovery and the mitigation of the negative effects of a crisis [ 16 ]. Moreover, recent studies conducted during the COVID-19 pandemic have identified the protective role of resilience in distress conditions among several populations, including university students [ 7 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social support from family, friends, community, and workplace may be protective. The study found that social support moderated the relationship between perceived uncontrollability and mental health symptom [32] and associated with lower COVID-19 psychological impact, though not with threat perception [33]. Previous study founded that psychological distress during the COVID-19 pandemic were having a poor self-perception of health, having diarrhea, having headache, having muscle pain, and having had casual contact with an infected person [34].…”
Section: Discussionmentioning
confidence: 81%
“…The score ranges of psychological distress; mild level (≤ 51), moderate level (52-81), and severe level (≥82). Then, the score ranges of coping; mild level (≤ 28), moderate level (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), and high level (≥46).…”
Section: Instrumentsmentioning
confidence: 99%
“…Social support from family, friends, community, and workplace may be protective. The study found that social support moderated the relationship between perceived uncontrollability and mental health symptom [32] and associated with lower COVID-19 psychological impact, though not with threat perception [33]. Previous study founded that psychological distress during the COVID-19 pandemic were having a poor self-perception of health, having diarrhea, having headache, having muscle pain, and having had casual contact with an infected person [34].…”
Section: Discussionmentioning
confidence: 81%
“…The score ranges of psychological distress; mild level (≤ 51), moderate level (52-81), and severe level (≥82). Then, the score ranges of coping; mild level (≤ 28), moderate level (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), and high level (≥46).…”
Section: Instrumentsmentioning
confidence: 99%